Gambaran pengetahuan, sikap, dan tindakan dokter keluarga terhadap penyakit ginjal kronis di Sulawesi Utara - EUGENIUS AGRO PALOBO; Frelly Valentino Kuhon; Dina Victoria Rombot (UNIVERSITAS SAM RATULANGI, 2026)
Background: Chronic kidney disease (CKD) is a major global health problem with increasing morbidity and mortality. Family physicians, as the frontline providers in primary health care, play an important role in the prevention, early detection, and initial management of CKD. Adequate knowledge, positive attitudes, and appropriate practices of family physicians regarding CKD are expected to reduce disease progression and related complications. Aim: To describe the knowledge, attitudes, and practices of family physicians toward chronic kidney disease in North Sulawesi. Methods: This study is a descriptive study with a cross-sectional research design. Results: The level of knowledge of family physicians in North Sulawesi was predominantly good, with 89 physicians (97.8%) in the good category and 2 physicians (2.2%) in the fair category. All respondents (91 physicians; 100%) had good attitudes toward CKD. The level of practice was mostly good, with 88 physicians (96.7%) in the good category, 1 physician (1.1%) in the fair category, and 2 physicians (2.2%) in the poor category. Conclusion: The overall levels of knowledge, attitudes, and practices of family physicians toward chronic kidney disease in North Sulawesi was categorized as good.